Laparoscopic Evaluation of Primary and Secondary Subfertility - Kasem, Setara Binte; Sultana, Nilufer; Begum, Ferdousi; Razzaque, Shaikh Abdur; Adiba, Raisa; Anika, Selma (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Prevalence of subfertility in industrialized countries has been quoted as 20%,and seems to be on the rise. Traditional way to assess the uterine cavity, tubal structure andtubal patency was hysterosalphingography but it is now been largely superseded bylaparoscopy and hysteroscopy. With the objective of this study was to highlight the role oflaparoscopy in establishing the diagnosis of primary and secondary female subfertility anddifferent therapeutic procedure done. Method: This cross sectional study was conducted in the Subfertility and ReproductiveMedicine Unit of Gynae and Obstetrics department of Dhaka Medical College Hospital, Dhakafrom January 2015 to June 2018. Total 4256 sub fertile patients attended the Infertility OPD.Out of these 215 patients were selected for laparoscopy. Those patients who hadcontraindication for laparoscopy were excluded from study. Detailed laparoscopic findingswere recorded. Results: Out of 125 selected sub fertile patients 136 (63.26%) patients were in primarysubfertility group while 79 (36.74%) patients were in secondary subfertility group. In primarysubfertility group(n=136), most common laparoscopic finding was PCO in 44 (32.34%) patientsfollowed by peritubal and periovarian adhesions in 24 (17.65%) patients, Bilateral tubalblock in 23(16.91%) patients, Endometriosis in 15(11.03%), Unusual tortuous and lengthytube in 15(11.03%) patients, fibroid in 11(8.09%) patients, Mullerian agenesis and hypoplasiain 3(2.21%) cases. No visible abnormality found in 22(16.18%) cases.The commonest finding by laparoscopy in patients with secondary infertility were PCO in 18(22.78%) patients and peritubal and periovarian adhesions in 18 (22.78%) patients, followedby Bilateral tubal block in 12(15.19%) patients, fibroid uterus in 12(15.19%) patients,Endometriosis in 10(12.66%), Genital tuberculosis in 3(1.40%) cases. No visible abnormalityfound in 12(15.19%) cases.Various laparoscopic procedure like Ovarian drilling. Adhesiolysis, ovarian cystectomy, cystpuncture, salphingostomy, Myomectomy. Conclusion: Laparoscopy helped us to detect and treat important clinical condition in bathprimary & secondary sub fertility. Bangladesh J Obstet Gynaecol, 2018; Vol. 33(2) : 143-148